Martyrdom and sacrifice in Islam theological, political and social contexts - Hatina, Meir; Litvak, Meir (London New York I.B. Tauris, 2017)
Martyrdom in the Muslim world is increasingly integral to conversations about international security. Over the years, the belief system around self sacrifice has become key to understanding the Middle East and its political relationships with the West, although much of the literature and conversation has been restricted to modern concepts of jihadism. The recent spate of scholarship relating to suicide bombers and jihadists studies these concepts without a broader understanding of the principle of martyrdom. This work expands on the chronology of self-sacrifice within Islam and contextualises the use of suicide bombings using details of the rise of martyrdom in places such as Iraq, Lebanon, Chechnya and Pakistan. It historicises the background in which 'jihad' has been glorified while also exploring contemporary methods of recruitment, like the use of the Internet.
part 3: Culture of martyrdom. Other ʻAshuraʼ : the martyrdom of Fatima in contemporary Shiʻi discourse / Liora Hendelman-Baavur -- Martyrdom, Shiʻa Islam, taʻziya : political symbolism in Shiʻa Islam / William O. Beeman -- Warrior saints : ʻAbdallah ʻAzzam's reflections on jihad and karamat / Meir Hatina -- Tales from the crypt : jihadi martyr narratives for online recruitment / Nico Prucha -- Use and genre of hudaʼ (uplifting battle songs) versus anashid (hymns of praise) in jihadi indoctrination and death rites / Philipp Holtmann
Includes bibliographical references (pages 327-350) and index.
Keywords: Suicide bombers; Martyrdom -- Islam; Death -- Religious aspects -- Islam; Self-sacrifice -- Religious aspects -- Islam